2021 IEEE International Conference on Mechatronics (ICM) 2021
DOI: 10.1109/icm46511.2021.9385677
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Capacitor-based Charge Estimators for Piezoelectric Actuators

Abstract: This paper focuses at charge estimators of piezoelectric actuators with a sensing capacitor. They have been claimed in the literature to be outperformed by their newly emerged competitors, charge estimators with a sensing resistor, widely known as digital charge estimators. This paper proposes a digital implementation of capacitor-based estimators and compares them with resistor-based ones both analytically and experimentally. Although, the sensing capacitors are normally bulkier than the sensing resistors use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(68 reference statements)
0
0
0
Order By: Relevance
“…Experiments have demonstrated that the position of a piezoelectric actuator is proportional to its electric charge for an extensive operating area [21][22][23]. Therefore, a charge estimator can replace a costly and troublesome accurate position/displacement sensor; this motivates research on charge estimation for piezoelectric actuators [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have demonstrated that the position of a piezoelectric actuator is proportional to its electric charge for an extensive operating area [21][22][23]. Therefore, a charge estimator can replace a costly and troublesome accurate position/displacement sensor; this motivates research on charge estimation for piezoelectric actuators [24,25].…”
Section: Introductionmentioning
confidence: 99%